Aplikasi Sistem Pakar untuk Diagnosa Penyakit Hipertiroid dengan Metode Inferensi Fuzzy Mamdani - Kamsyakawuni, Ahmad; Gernowo, Rachmad; Sarwoko, Eko Adi (Universitas Diponegoro, 2012)
Medical diagnosis is a complex issue that is influenced by various factors and settlement involving all the capabilities of experts, including expert intuition owned. Diagnosis of thyroid disease is difficult, because the symptoms of thyroid disease can vary greatly, depending on the ups and downs of thyroid hormones. This study applies an expert system for diagnosis of hyperthyroidism using Mamdani fuzzy inference methods. Expert system expertise needed to gain knowledge from the experts in resolving hyperthyroidism diagnosis while Mamdani fuzzy inference is used for the processing of knowledge in order to obtain the consequence or conclusion which is the result of diagnosis. The process ofMamdani fuzzy inference in this study began with the formation of fuzzy set continued with the application process implications functions, then the composition rule and ending with defuzzyfication process. An expert system for the diagnosis of hyperthyroidism that has been applied with a symptom score of the input data, the results of the blood t ests TSHs level and FT4 levels, output data in the form of diagnosis, the diagnosis has been successfully for tested the input data, with an accuracy of 95.45%.Keywords: Expert systems; Fuzzy inference Mamdani; Hyperthyroidism